(3fXe GdeYdheGJ GdeMhSHI hOYe GJNGP GdbQGQs - (3YHO GddGg GHQGgje(B, (3Gdabjs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2012)
(3GdfXGe(B- (3JMdjd hJUeje GdfXe hGdJUeje GdJYdjej(B- (3fXe OYe GdbQGQ(B- (3CfXeI GdeYdheGJ(B- (3eMdd GdfXes
(3GdeQGLY U(B.211s
Keywords: (3GJNGP GdbQGQs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s